Development of portable defocusing micro-scale spatially offset Raman spectroscopy. Issue 10 (8th April 2016) - Realini, Marco; Botteon, Alessandra; Conti, Claudia; Colombo, Chiara; Matousek, Pavel
Abstract : We present, for the first time, portable defocusing micro-Spatially Offset Raman Spectroscopy (micro-SORS). Abstract : We present, for the first time, portable defocusing micro-Spatially Offset Raman Spectroscopy (micro-SORS). Micro-SORS is a concept permitting the analysis of thin, highly turbid stratified layers beyond the reach of conventional Raman microscopy. The technique is applicable to the analysis of painted layers in cultural heritage (panels, canvases and mural paintings, painted statues and decorated objects in general) as well as in many other areas including polymer, biological and biomedical applications, catalytic and forensics sciences where highly turbid stratified layers are present and where invasive analysis is undesirable or impossible. So far the technique has been demonstrated only on benchtop Raman microscopes precluding the non-invasive analysis of larger samples and samples in situ . The new set-up is characterised conceptually on a range of artificially assembled two-layer systems demonstrating its benefits and performance across several application areas. These included stratified polymer sample, pharmaceutical tablet and layered paint samples. The same samples were also analysed by a high performance (non-portable) benchtop Raman microscope to provide benchmarking against our earlier research. The realisation of the vision of delivering portability to micro-SORS has a transformative potential spanning across multiple disciplines as it fully unlocks, for the first time, the non-invasive and non-destructive aspects of micro-SORS enabling it to be applied also to large and non-portable samples in situ without recourse to removing samples, or their fragments, for laboratory analysis on benchtop Raman microscopes.